2022
DOI: 10.3390/molecules27103269
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin Reduces Inflammation and Protects Gut Microbiota in Broilers

Abstract: The aim of this study was to investigate the effects of quercetin on inflammatory response and intestinal microflora in broiler chicken jejuna. A total of 120 broiler chickens were allocated into 3 groups: saline-challenged broilers fed a basal diet (CTR group), lipopolysaccharide (LPS)-challenged broilers fed a basal diet (L group) and LPS-challenged broilers fed a basal diet supplemented with 200 mg/kg quercetin (LQ group). Our results showed that LPS significantly increased expression of tumor necrosis fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…Butyricimonas, Marvinbryantia, and Oscillibacter can produce butyrate, which participates in regulating gut permeability and induces the inflammatory response (Jang et al, 2020;Chen B. D. et al, 2021;Chen Z. et al, 2021;Liu et al, 2022). Prior studies have reported that the abundance of Peptococcus increases when intestinal inflammation occurs, indicating its proinflammatory effects (Sun et al, 2022). The exact mechanism of Peptococcus on the pathogenesis of PPH warrants verification studies.…”
Section: Discussionmentioning
confidence: 99%
“…Butyricimonas, Marvinbryantia, and Oscillibacter can produce butyrate, which participates in regulating gut permeability and induces the inflammatory response (Jang et al, 2020;Chen B. D. et al, 2021;Chen Z. et al, 2021;Liu et al, 2022). Prior studies have reported that the abundance of Peptococcus increases when intestinal inflammation occurs, indicating its proinflammatory effects (Sun et al, 2022). The exact mechanism of Peptococcus on the pathogenesis of PPH warrants verification studies.…”
Section: Discussionmentioning
confidence: 99%
“…Flavonols have numerous biological functions. For instance, quercetin enhances the antioxidant capacity of broilers' intestines, alleviates intestinal inflammatory reactions, regulates the internal intestinal environment, maintains the integrity of the intestinal barrier, and improves the structure and morphology of the intestinal tract (15)(16)(17). Rutin exhibits antioxidant and anti-inflammatory effects by inhibiting the production of reactive oxygen species and cell apoptosis (18).…”
Section: Discussionmentioning
confidence: 99%
“…Quercetin is a type of natural flavonoid isolated from various fruits and vegetables ( Mirazimi et al, 2022 ). Previous studies have shown that quercetin possesses many functions, including anti-cancer, anti-oxidative, and anti-inflammatory properties ( Pinheiro et al, 2021 ; Yin et al, 2021 ; Sun et al, 2022 ). Wang et al found that quercetin can activate the autophagy pathway through SIRT1 so as to reduce the level of ROS and alleviate apoptosis and extracellular matrix degeneration ( Wang D. et al, 2020 ).…”
Section: Phytochemicals For the Treatment Of Idd By Targeting Inflamm...mentioning
confidence: 99%